Cytokine Reduction in the Treatment of Joint Conditions - J. D. Sipe; J. Martel-Pelletier; I. G. Otterness; J.-P. Pelletier (Mediators of Inflammation)
The destruction of joints caused by rheumatoid arthritis and osteoarthritis is characterized by an imbalance of enzyme catalysed cartilage breakdown and regeneration. A complex cytokine network perpetuates joint conditions by direct regulation of metalloproteases, by indirect recruitment of cells that secrete degradative enzymes, and by inhibition of reparative processes. The destructive action of cytokines such as interleukin-1, interleukin-6 and tumour necrosis factor-α can be modulated at multiple points associated either with cytokine production or with cytokine action. Potential agents for cytokine reduction include selective anti-cytokine antibodies, anticytokine receptor antibodies, cytokine receptor antagonist proteins, and soluble and chimeric cytokine receptor molecules. Pharmacologic regulation of IL-1 and TNFα remain primary targets for treatment of arthritis, and results of early clinical trials are promising. However, the results of long-term clinical trials will be required to support the value of anti-cytokine therapy in treatment of arthritis.